A case series of comorbidities seen in bullous pemphigoid - Koneru, Yamini; Wilson, Anushka; Patil, Sharmila (International Journal of Research in Dermatology, 2024)
Bullous pemphigoid (BP) is an autoimmune skin blistering disease commonly seen in the elderly which is associated with increased morbidity. The association of BP with comorbidities, especially cardiovascular, neurological, type 2 diabetes mellitus (T2DM) and has been seeing a rising trend in the recent years, not only with the underlying condition but also the drugs associated. A systematic literature review was conducted to identify and analyze the comorbidities prevalent in patients with BP.